Between Scholarship and Dissidence: The Dissident Historical Collection Pamiat΄ (1975–1982). Issue 4 (31st January 2018) - Martin, Barbara; Sveshnikov, Anton
Abstract : This article examines the history of the Soviet dissident historical collection Pamiat΄ through the lens of liminality. It argues that the publication sought to bridge the gap between dissident and professional scholarship, between grassroots memory collection, with its emphasis on the witness's voice, and historical research's reliability and "scientificity." Although Pamiat΄ was inspired by earlier dissident historiographical projects and its editorial team was closely linked to the human-rights movement, its ambitions of objectivity and representativeness also connect it to later Perestroika projects based on citizen involvement, such as Memorial . Pamiat΄ s ambiguous identity and claim to neutrality may have delayed the Soviet authorities' response to it, but repression eventually hit the publication. By putting into question the state's monopoly on historical scholarship and connecting readers and contributors across the Iron Curtain, Pamiat΄ had clearly overstepped the boundaries of the permissible and acquired a political meaning it disingenuously claimed not to have.